Poly-L-lactic acid for global facial volumization (Canadian Dermatology Today, 2022)
Biostimulatory fillers, such as poly-L-lactic acid (PLLA), have been increasingly used to address facial volume deficiency in recent years. PLLA is an absorbable, semi-permanent soft tissue filler that restores volume by stimulating collagen formation. It is comparable to facial fat grafting. PLLA is approved by Health Canada for facial fat restoration due to antiretroviral therapy-induced lipoatrophy. It is also approved for increasing the volume of depressed areas due to skin creases, wrinkles, folds, and for skin aging. In real-world use, PLLA has also been used in off-label areas, including the neck, dorsal hands, abdomen, thighs, and the gluteus. Multiple studies have confirmed the high patient satisfaction rate, excellent safety profile, and efficacy of PLLA for treating the aging face.